Implementasi Metode Bercerita Bahasa Arab untuk Meningkatkan Pemahaman Kosa Kata : (Studi Kasus Siswa MTs Kelas VII Al-Ma’li Bojonegoro) - Umi ma'rifatul fadhilah; Amrini Shofiyani (Sekolah Tinggi Agama Islam Syaichona Moh. Cholil Bangkalan, 2023)
This study aims to evaluate the efficiency of applying the storytelling approach in teaching Arabic to optimize the vocabulary of class VII students at MTs Plus Al-Maáli Bojonegoro. With a quantitative approach, the experimental design type is one group pretest-posttest and uses observation, interviews, questionnaires, and tests as instruments. Analysis of pretest and posttest results by comparing the average scores. There was significant progress in student learning outcomes, with an initial pretest average score of 69.45 increasing to 83.63 in the posttest. The positive relationship between learning methods and students at MTs Plus Al-Maáli Bojonegoro is also proven through the questionnaire to determine the most appropriate method. The results of the t-test show that the value of Asymp Sig. (2-tailed) is 0.000000003 < 0.05, which indicates that the hypothesis is accepted. Thus, after applying this learning method, there is a significant difference in the learning outcomes of class VII students at MTs Plus Al-Maáli Bojonegoro. It can be concluded that implementing the storytelling method in teaching Arabic succeeded in increasing the learning achievement of class VII students at MTs Plus Al-Maáli Bojonegoro in Arabic subject.